A rare cause of intestinal obstruction in a newborn: Congenital band compression - Aydin, Emrah (North Clin Istanb, 2016)
Congenital band compression syndrome should be considered in cases diagnosed prenatally or postnatally as intestinal obstruction. Presently described is a report of newborn admitted to hospital with abdominal distension and bilious vomiting. A suspected intestinal obstruction had been diagnosed in prenatal examination. Surgery revealed congenital band compressing ileal segments and preventing transmission of intestinal content. Band was successfully removed and intestinal integrity is intact.